Simultaneous analytical determination of Methyl salicylate and thymol in selected Malaysian traditional medicines / Muhammad Shahariz Mohamad Adzib - Muhammad Shahariz , Mohamad Adzib (2020)
Various topical formulations comprise of methyl salicylate and thymol due to their analgesic and anti-inflammatory properties. The huge demand has led traditional medicines being susceptible to adulteration with synthetic drugs or their analogues to enhance their efficacy and to minimise the cost of obtaining the limited natural substance. The objectives of this study are to analyse a suitable analytical method for simultaneous determination of methyl salicylate and thymol in selected Malaysian traditional medicines using High Performance Liquid Chromatography (HPLC) and to screen the selected Malaysian traditional medicines for possible methyl salicylate and thymol adulteration using the analytical method. Most literature search showed the determination of methyl salicylate and thymol as an individual compound or in combination with other compounds instead of both being detected simultaneously using a single method. Methyl salicylate and thymol were separated at about 3.8 and 6.2 min, respectively at a flow rate of 1 mL/min on C8 column with methanol and water (65:35) as the mobile phase, column temperature of 35°C and detector wavelength of 230 nm within 9 minutes of run time. Method validation was conducted and this method was rapid, sensitive, linear, specific, precise and accurate. The validated method was applied for screening of methyl salicylate and thymol in 10 samples of liniment and ointment. Half of the samples were detected with methyl salicylate and none with thymol. Majority of the positive samples were unregistered traditional medicines. Hence, the method can be adopted for routine quality control analysis of methyl salicylate and thymol in traditional medicines.